2011
DOI: 10.2528/pierc11042712
|View full text |Cite
|
Sign up to set email alerts
|

Steerable Antenna Using Algorithm Based on Downhill Simplex Method

Abstract: Abstract-Electronically steerable passive array radiator(ESPAR) antennas are expected to gain prominence in the field of wireless communication, because they can be steered toward a desired signal and they can eliminate interference; in addition, they have a very simple architecture that has significantly low power consumption and are inexpensive to manufacture. In this paper, we proposed an ESPAR antenna that has fastest convergence time. The downhill simplex method is used to maximize the correlation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We proposed using a defogger as the RSAA by placing several ports on it [4]. We used the simplex method to achieve robust beamforming with rapid convergence [5]. In addition, we confirmed that the proposed antenna was able to operate in multiband [6].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We proposed using a defogger as the RSAA by placing several ports on it [4]. We used the simplex method to achieve robust beamforming with rapid convergence [5]. In addition, we confirmed that the proposed antenna was able to operate in multiband [6].…”
Section: Introductionmentioning
confidence: 86%
“…If the correlation coefficient between the HGI and TGI of the received signal becomes large, the delayed signal has to be cancelled. We used the simplex method in which the correlation was the objective function [5].…”
Section: A Shared Aperture Based On a Rear Defoggermentioning
confidence: 99%
“…The linear antenna array consists of M number of elements with inter-element distance d, and an incident wave at an angle of ϕ. The Array Factor AF for this array is [18][19][20] …”
Section: The Misalignment Effectmentioning
confidence: 99%
“…Modified algorithms were developed to reduce the computational load by reducing the required vector length such as the Recursive LMS (R-LMS ). Nevertheless, this algorithm should wait until the required number of symbols is assembled to perform training [9,18]. Combing this algorithm with modulus detecting algorithms such as Constant Modulus Algorithm (CMA), Decision Direct Algorithm (DDA), or Conjugate Gradient Method (CGM ) will produce the blind adaptive beamforming algorithms such as LMS -CMA, LMS -DDA, RLMS -CMA, .…”
Section: Introductionmentioning
confidence: 99%
“…Various algorithm has been used in ESPAR such as steepest descent, direct search, genetic algorithm and stochastic beamforming [4,5] In this study, an electronically steerable antenna is designed using a slotted array antenna. The downhill simplex method algorithm has been chosen because it has the fastest convergence time [6][7][8].…”
Section: Introductionmentioning
confidence: 99%